Legal Culture, Sociopolitical Origins and Professional Careers of Judges in Mexico - Aguiar Aguilar, Azul A. (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
XI, 179 p. 24 illus., 22 illus. in color.